Synchronization of energy and nitrogen release in the rumen: A modelling approach for forages - Lavrencic A.; Stefanon B.; Mills C.R.; Susmel P. (Recent advances in small ruminant nutrition, 1997)
In the study, 2 grasses and 2 legumes were harvested at 2 stages of growth. Duplicate samples were incubated in sacco in the rumen of 3 mature, fistulated cows for 2, 4, 8, 16, 24, 48 and 72 hours, and the degradability of DM and nitrogen was measured. Degradability data were fitted with a Gompertz model, which offers the opportunity of studying two aspects of rumen degradation: degradation kinetics, represented as cumulative curves and degradation rate kinetics. The synchronicity in the release of nitrogen and dry matter or structural carbohydrates was calculated from the ratio between the quantity of nitrogen and dry matter or fibre degraded per unit time, using the first derivative of the Gompertz equation. This provided a dynamic description of the degradation process for each forage which would allow the combination of feeds in a ration to maintain these ratios constant throughout the rumen digestion process.
Seminar of the FAO-CIHEAM Network of Cooperative Research on Sheep and Goats, Subnetwork on Nutrition, 24-26 Oct 1996, Rabat (Morocco)